Zoonoses (Project 1): Wildlife/domestic livestock interactions - Jones, B.; McKeever, Declan J.; Grace, Delia; Pfeiffer, Dirk U.; Mutua, Florence K.; Njuki, Jemimah; McDermott, John J.; Rushton, Jonathan; Said, Mohammed Yahya; Ericksen, Polly J.; Kock, R.; Alonso, Silvia (International Livestock Research Institute, 2011)
The objective of this study was to synthesise the best available scientific knowledge about zoonotic disease transmission through livestock and wildlife interaction (direct or indirect), with emphasis on risk factors, drivers and trajectories of transmission, as well as promising interventions for controlling important zoonoses, based on managing the interaction between domestic livestock and wildlife.